2011
DOI: 10.1016/j.radonc.2011.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intensity-modulated radiotherapy, adaptive radiotherapy, proton radiotherapy, and adaptive proton radiotherapy for treatment of locally advanced head and neck cancer

Abstract: Background and Purpose Various radiotherapy planning methods for locally advanced squamous cell carcinoma of the head and neck (SCCHN) have been proposed to decrease normal tissue toxicity. We compare IMRT, adaptive IMRT, proton therapy (IMPT), and adaptive IMPT for SCCHN. Materials and Methods Initial and re-simulation CT images from 10 consecutive patients with SCCHN were used to quantify dosimetric differences between photon and proton therapy. Contouring was performed on both CTs, and plans (n=40 plans) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
103
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(105 citation statements)
references
References 37 publications
1
103
0
1
Order By: Relevance
“…Although dose distribution change for critical organs was not so large in the NCPS cancer patients as a whole, some patients in our study showed unexpected change which should not be overlooked. We propose that repeat imaging and dose recalculation is necessary, and that if adaptive treatment planning can be performed it should be positively adopted to avoid unexpected higher dose distribution to critical organs as suggested by previous studies [12,13].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although dose distribution change for critical organs was not so large in the NCPS cancer patients as a whole, some patients in our study showed unexpected change which should not be overlooked. We propose that repeat imaging and dose recalculation is necessary, and that if adaptive treatment planning can be performed it should be positively adopted to avoid unexpected higher dose distribution to critical organs as suggested by previous studies [12,13].…”
Section: Discussionmentioning
confidence: 96%
“…However, as that increase had large variations, they suggested repeat imaging, dose recalculation, and, if required, adaptive planning to ensure sufficient target coverage and to avoid unwanted exposure of critical organs. Simone et al compared intensity-modulated proton radiotherapy (IMPT) and adaptive IMPT for head and neck cancers, and reported that although dose reduction of critical organs in adaptive IMPT was less clinically significant, care must be taken to account for these changes or to otherwise ensure accuracy of the beam range because proton plans are sensitive to interfractional changes in tumor volume and patient anatomy [13]. In recent years, adaptive treatment planning for head and neck cancers has increased, mostly in X-ray radiotherapy [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Intensity modulated proton therapy (IMPT) planning studies support this hypothesis by demonstrating improved sparing of OARs compared to IMRT. 2,3 The large anatomical changes which may be observed during fractionated H&N radiation therapy 4 suggest that the use of repeated computed tomography (CT) scanning may be essential during IMRT (Ref. 5) and IMPT (Ref.…”
Section: Introductionmentioning
confidence: 99%
“…A future perspective for ensuring good target coverage while sparing OARs, would be adaptive radiotherapy and, farther away, adaptive proton radiotherapy (31,32).…”
Section: Discussionmentioning
confidence: 99%